Prevalence and Risk Factors of Sports Injuries in Papuan Athletes - Fazryani Mazita Torano; Rio Wakhid Hujjatul Islam; Cicilia Kubiari; Fellisa Kogoya (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
Sports injuries are a serious issue frequently experienced by athletes, especially in high-intensity sports such as rugby, karate, and softball. Sports-related injuries not only impair athletic performance but can also threaten the longevity of an athlete’s career. The limited availability of empirical data concerning the prevalence and contributing factors of sports injuries among Papuan athletes served as the primary motivation for this research. This study was designed to identify the prevalence, types, anatomical locations, and potential risk factors associated with injuries across three sports disciplines. Employing a quantitative descriptive design with an ex post facto approach, the research involved 56 PON athletes. Data were collected through structured questionnaires and analyzed using chi-square and logistic regression tests. The results showed that 83.9% of athletes experienced injuries, mainly grade 1–2 strains and abrasions, with the hip and head being the most affected areas. Rest was identified as the most significant factor influencing sports injuries (p = 0.044; OR = 0.061). The study found that most reported injuries were mild to moderate strains, primarily affecting the pelvis and head, with rest identified as the most significant factor influencing injury incidence. Therefore, effective recovery management and an integrated prevention approach balancing training, rest, psychological support, and technical supervision are essential to reduce injury risks among athletes.